Effect of Diet Types and Slaughter Ages on Carcass Characteristics of the Domestic Rabbits in Humid Southern Nigeria - Oteku, I.T.; Igene, J.O. (Pakistan Journal of Nutrition, 2005)
This study was conducted to assess the effect of feed types (rabbit grower’s mash, chicken grower’s mash and chicken layer’s mash) and age at slaughter (10wks, 13wks and 16wks) on the characteristics of rabbit fresh meat. The parameters evaluated were the pH change during slaughtering (during rigor mortis development) and carcass characteristics in terms of dressed weights, dressing percentage, organ weights, physical cuts and meat/bone ratio to establish practice viability. On the average, it took the rabbit meat 4.76 hours to attain the ultimate pH of 5.69 at 2±2 C. The dressed carcass weight, on o the average was 47.9% of live weight. Dressed carcass percentage was significantly influenced by slaughter age with rabbit slaughtered at 10 weeks having lower value than that of 13 and 16 weeks slaughter ages. Slaughter age influenced the absolute weight of each physical cut. As the slaughter age increased, the average meat/bone ratio of 3.46 increased significantly. Diets did not have significant effect on meat/bone ratio and on the relative organ weights. Moistened chicken feeds (Layers and Growers mash) could be fed to rabbits with heavy forage supplementation for optimal rabbit meat production.